Inhibition of PI3K suppresses propagation of drug-tolerant cancer cell subpopulations enriched by 5-fluorouracil - Kaoru Ishida; Chie Ito; Yukimi Ohmori; Kohei Kume; Kei A. Sato; Yuka Koizumi; Akari Konta; Takeshi Iwaya; Mamoru Nukatsuka; Takashi Kobunai; Teiji Takechi; Satoshi S. Nishizuka (Scientific Reports, 2017)
Abstract Drug-tolerant cancer cell subpopulations are responsible for relapse after chemotherapy. By continuously exposing the gastric cancer cell line MKN45 to 5-FU for >100 passages, we established a 5-fluorouracil (5-FU)-tolerant line, MKN45/5FU. Orthotopic xenografts of MKN45/5FU cells in the stomach of nude mice revealed that these cells had a high potential to metastasize to sites such as the liver. Levels of phosphorylated phosphatidylinositide 3-kinase (PI3K) increased both in 5-FU-tolerant subpopulations according to the 5-FU dose, and in gastric submucosal orthotopic xenografts of MKN45/5FU cells. Sequential administration of 5-FU and a PI3K inhibitor, GDC-0941, targeted the downstream ribosomal S6 kinase phosphorylation to significantly suppress 5-FU-tolerant subpopulations and tumor propagation of orthotopic MKN45/5FU xenografts. These results suggest that administration of 5-FU followed by GDC-0941 may suppress disease relapse after 5-FU-based gastric cancer chemotherapy.